2021
DOI: 10.1111/echo.15215
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical myocardial dysfunction in patients recovered from COVID‐19

Abstract: Background: Myocardial injury (MI) can be detected during the acute phase of Coronavirus disease 19 and is associated with a dismal prognosis. Recent imaging studies described the persistence of cardiac abnormalities after the recovery. The aim of the study was to investigate the spectrum of cardiac abnormalities at mid-term follow-up in patients recovered from COVID-19 using clinical assessment, laboratory tests, and imaging evaluation with comprehensive echocardiography.Methods: This is an observational, cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 37 publications
0
19
0
2
Order By: Relevance
“…Studies showing that biventricular diastolic functions are adversely affected in COVID-19 patients are included in the literature. [23][24][25] In a recent study, cardiac performance was followed for 6 months in hospitalized patients with COVID-19, and evidence of myocardial injury, and diastolic dysfunction was reported to be common. However, they reported that diastolic dysfunction was not affected in the 6month follow-up of COVID-19 patients without cardiac involvement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies showing that biventricular diastolic functions are adversely affected in COVID-19 patients are included in the literature. [23][24][25] In a recent study, cardiac performance was followed for 6 months in hospitalized patients with COVID-19, and evidence of myocardial injury, and diastolic dysfunction was reported to be common. However, they reported that diastolic dysfunction was not affected in the 6month follow-up of COVID-19 patients without cardiac involvement.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, systolic and diastolic functions may be adversely affected. Studies showing that biventricular diastolic functions are adversely affected in COVID‐19 patients are included in the literature 23–25 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ischemic injury pattern, defined as having either sub-endocardial or transmural late gadolinium enhancement (LGE) on CMR or inducible ischemia on adenosine stress test, was found in 66% of patients with no prior history of coronary disease. Another study comparing patients who developed myocardial injury, defined by high-sensitivity troponin T (hsTnT) elevation exceeding the 99th percentile, during hospitalization for COVID-19 infection versus those without myocardial injury found that patients with myocardial injury had higher frequency of impaired diastolic function, larger left atrial size, and higher values of pulmonary artery pressure at three-month follow-up as compared to the group that did not develop myocardial injury during hospitalization for COVID-19 infection [ 34 ]. Another prospective cohort study evaluating 159 patients found that at 4–9 weeks post-hospitalization for COVID-19 infection, patients recovering from COVID-19 were at greater risk of developing myocardial scarring and persistent cardio-renal dysfunction as compared to matched control [ 35 ].…”
Section: Myocardial Injury and Ischemic Heart Diseasementioning
confidence: 99%
“…[ 23 ],[ 24 ] Occasionally, the damages can be subclinical, as evident by worse left ventricular global longitudinal strain and diastolic function in patients recovered from COVID-19 infection. [ 26 ] These may have long-term consequences given the huge number of COVID-19 survivors and the pandemic seems to be long lasting.…”
Section: Impact Of St Elevation Myocardial Infarction On Patients Suf...mentioning
confidence: 99%